PENGARUH SHARIAH RELATIONSHIP MARKETING DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP WORD OF MOUTH NASABAH BANK JATIM SYARI’AH KEDIRI - Antoro, Deny Yudi; Setiawan, Didik (IAIN Tulungagung, 2020)
This research is designed to analyze the effect of several factors, such as shariah relationship marketing, service quality, customer satisfaction and word of mouth in the surrounding of customer Islamic bank industry. Survey and explanatory methods are used in the research by applying purposive proportional sampling technique. The technique of data analysis is descriptive, confirmatory factor and structural technique data analysis using Structural Equation Model ( SEM). The result of validity and reliability test on all items proves that all of those item are valid and reliable. Overall goodness of fit shows that the model used in this research meets the requirement to be a good model. The result of the hypothesis testing on confirmatory factors shows that the estimated factor dimension has signifigant contribution on latent variables among which are shariah relationship marketing, service quality, customer satisfaction and word of mouth. The result of structural model hypothesis testing are as follows : 1) it has been proved that shariah relationship marketing and service quality have significant effect on customer satisfaction. 2) it has been proved that shariah relationship marketing and service quality have significant effect on word of mouth. 3) it has been proved that customer satisfaction have significant effect on word of mouth. 4) it has been proved that shariah relationship marketing and service quality have significant effect on word of mouth through customer satisfaction. Keywords: Shariah relationship marketing, Service quality, Customer satisfaction and Word of mouth.